In situ fabrication of bendable epitaxial metal–organic framework films via spraying. Issue 79 (15th September 2022) - Fan, Fuqiang; Zeng, Qingqi; Zhang, Zhihui; Zhang, Liying; Zhang, Xuemin; Wang, Tieqiang; Fu, Yu
Abstract : Epitaxial metal–organic framework (MOF) films have shown huge potential for use in separation applications. Abstract : Epitaxial metal–organic framework (MOF) films have shown huge potential for use in separation applications. Herein, bendable epitaxial MOF films are fabricated via spraying. The synthesized MOF films show excellent oil-in-water emulsion separation performance even after being bent for multiple times at high curvatures.